Angiogenesis and Proliferation Index in Patients with Acute Leukemia: A Prospective Study. (31st March 2014) - Jothilingam, Prabhavati; Basu, Debdatta; Dutta, Tarun K.
Abstract : Angiogenesis and proliferation as measured by microvessel density (MVD) and proliferation index (PI) are essential correlates of malignancy. The aim of our study was to evaluate difference between these values in AML and ALL and also to study the modulation in these parameters following achievement of remission in acute lymphoblastic leukemia. Differences between adult and adolescent cases of acute leukemia in relation to these values were also studied. We also tried to assess the relationship between angiogenesis and proliferation. Fifty-five patients with acute leukemia were included in the study. Trephine biopsies were immunostained with CD34 and factor VIIIrAg to demonstrate angiogenesis measured as MVD. Immunostaining with PCNA and Ki-67 was done to study proliferation. We found a significant increase in MVD and PI in cases when compared with controls (P < 0.0001 ). In addition cases with ALL had a significantly higher MVD compared to those with AML (P < 0.01 ). The patients with ALL who went into remission showed a significant reduction in MVD; PI remained high. The cases which did not achieve remission showed no significant reduction in either MVD or PI. All adolescent cases of ALL were similar to adults with respect to MVD and PI.